Um olhar sobre a concepção de professor adotada nas propostas curriculares implantadas no curso de História da UFPA em 1988 e 2006 - COSTA, Rildo Ferreira da (2008)
The present study is about the teachers' formation and its interest is the investigation of this problem: what teacher conceptions are present in the curricular proposals of the History graduation course at UFPA (Federal University of Pará) implemented in 1988 and 2006? The relevance of this work is in the possibility to problematize the History teacher's formation and to supply subsidies to contribute to enlarge that debate in current University of History. The study has its methodological basis in the beginnings of the qualitative research, adopting as a procedure the data research and the accomplishment of semi-structured interviews. For such purpose, we looked for doing the analysis of official documents of the Federal Legislation about education; of the internal legislation of UFPA and particularly of the History course of that institution, articulating them to the theoretical references about formation and teacher's conception. The rising of documents was made at DAC (Department of Didactic-scientific Support), File of the Center of Philosophy and Humanities, Files of University of History and Internet. The information contained in the documentations were complemented with interviews accomplished with six teachers, that participated directly of the discussions and approval of the curricular proposals investigated. The results of the analyses done in the corpus evidence that the curricular reforms investigated suffered influence of the discussions that were happening in national level and its repercussion in the internal movement of UFPA and, particularly, in the course of History of that institution. The curricular proposal of 1988 presented a profile based at the "professional's of History" formation and a conception of technician-lineal teacher anchored in the beginnings of the technical rationality. The Pedagogic Political Project, implemented in the course of History in 2006 evidences a profile of "Teacher-historian" and intentionality for reflexive teacher's conception, that, however, it is questionable in reason of the absence of a pedagogic discussion based at the teacher's formation. The historical and pedagogic knowledge included in the two curricular proposals are not always coherent with the profile and the conception of teacher presents in the curricular proposals investigated, in reason of its graphic formatting and epistemological of the curricular structure.